Hybrid offset‐time and burst assembly algorithm (H‐OTBA) for delay sensitive applications over optical burst switching networks. (10th July 2014) - Yayah, Abdulsalam A.; Coulibaly, Yahaya; Ismail, Abdul Samad; Rouskas, George
Summary: Optical burst switching (OBS) is the most favourable switching paradigm for future all‐optical networks. Burst assembly is the first process in OBS and it consists of aggregating clients packets into bursts. Assembled bursts wait for an offset time before being transmitted to their intended destinations. Offset time is used to allow burst control packet reserve required resources prior to burst arrival. Burst assembly process and offset‐time create extra delay in OBS networks. To make OBS suitable for real time applications, this extra latency needs to be controlled. This paper proposes and evaluates a novel offset time and burst assembly scheme to address this issue. Constant bit rate (CBR) traffic that has stringent end‐to‐end delay QoS requirements is used in this study. The proposed scheme is called hybrid offset‐time and burst assembly algorithm (H‐OTBA). The objective of the paper is achieved by controlling maximum burst transfer delay parameters of CBR. The proposed scheme was evaluated via network simulation. Simulation results demonstrate that, H‐OTBA has effectively reduced end‐to‐end delay for CBR traffic compared with current solutions. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : The paper proposes an efficient hybrid burst assembly algorithm for optical burst switching (OBS) networks to reduce end‐to‐end delay. The aim is to make OBS suitable for real‐time and mission critical applications that have stringent delay requirements.